PERISTILAHAN DALAM PROSESI JADI MALI PADA MASYARAKAT DAYAK KERABAT PENYAPAT - Yustina, Intania; Simanjuntak, Hotma; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was conducted by analyzing the terminology in the Jadi Mali procession in the Dayak Kerabat Menyapat community with the aim of describing an inventory of terminology in the Jadi Mali procession in the Dayak Kerabat Penyepat community, describing the form of lingual units of terminology in the Jadi Mali procession in the Dayak Kerabat Penyapat community, describing the meaning of the term in the Jadi Mali procession for the Dayak Kerabat Penyapat community, and describes the plan for implementing the terminology in the Jadi Mali procession for the Dayak Kerabat Penyapat community. The method used is a descriptive method and a form of qualitative research. The data source for this research is the Dayak Kerabat Penyepat language which is used in the customs of the Dayak Kerabat Menyapa community. The data of this research are words and phrases. The technique used is literature study, face-to-face conversation, and note-taking. Data collection tools are documents, questionnaires, and note sheets. Based on the analysis conducted, there are 90 terminology in the Jadi Mali procession consisting of words (monomorphemic, polymorphemic, affixation, and compound words) and phrases. The form of learning implementation contained in the RPP is adjusted to the 2013 curriculum for grade VII junior high school in odd semesters